Predictors and consequences of negative physician attitudes toward HIV-infected injection drug users. - Ding, Lin; Landon, Bruce E; Wilson, Ira B; Wong, Mitchell D; Shapiro, Martin F; Cleary, Paul D (Archives of internal medicine, 2005)
We evaluated physicians' training, experience, and practice characteristics and examined associations between their attitudes toward human immunodeficiency virus (HIV)-infected persons who are injection drug users (IDUs) and quality of care.
Keywords: Adult; Attitude of Health Personnel; Cross-Sectional Studies; Female; HIV Seropositivity; Humans; Interviews as Topic; Job Satisfaction; Linear Models; Male; Middle Aged; Patient Satisfaction; Physicians; Quality of Health Care; Substance Abuse, Intravenous; United States